2005
DOI: 10.1021/ma051022e
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study on Thermal Shrinkage and Dimensional Stability Associated with Oriented Poly(lactic acid)

Abstract: Morphological features governing dimensional stability of variously processed poly(lactic acid) have been investigated. The exotherm observed near the glass transition temperature (Tg) is one of the most sensitive indicators reflecting structural changes as a function of temperature and time. A combination of spectroscopic and calorimetric techniques was used to analyze the amorphous chain conformation of deformed PLA samples. We found that nucleation-enhanced crystallization is the major contributor to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 27 publications
8
85
0
2
Order By: Relevance
“…The first heating scan of the T sample exhibited an intense exothermal peak right after T g due to chain rearrangement in the deformed amorphous regions. The post-T g exothermic peak was attributed to the cold crystallization and/or mechanical shrinkage of oriented non-crystalline domains [26,32]. The rearrangement of oriented amorphous chains into the crystalline phase increases the rubbery plateau modulus dramatically [41].…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The first heating scan of the T sample exhibited an intense exothermal peak right after T g due to chain rearrangement in the deformed amorphous regions. The post-T g exothermic peak was attributed to the cold crystallization and/or mechanical shrinkage of oriented non-crystalline domains [26,32]. The rearrangement of oriented amorphous chains into the crystalline phase increases the rubbery plateau modulus dramatically [41].…”
Section: Dynamic Mechanical Thermal Analysismentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA) have been used to ascertain the processing/crystallization effects on the fiber thermal [6,8,11,12,25,26] and thermomechanical properties [8,14,25]. Detailed thermomechanical analysis of the PLA fibers revealed storage modulus, E′, loss modulus, E″ and tan δ curves sensitivity to fiber structure.…”
Section: Introductionmentioning
confidence: 99%
“…And this main transition is suggested to be the origins of shrinkage in PLA fiber samples according to Aou and al. [2]. Concerning the heat of melting, studies in pure PLA containing less than 6% D [18] did not show a heat of crystallization on reheating process indicating that most of the crystallization process was completed during the quenching procedure.…”
Section: Thermal Analysismentioning
confidence: 90%
“…Some authors [17] found that the higher T g at higher L lactide contents could be explained by intrinsically greater chain stiffness. Others [2] declared that the exothermal observed near the glass transition temperature (T g ) is one of the most sensitive indicators reflecting structural changes as a function of temperature and time. And this main transition is suggested to be the origins of shrinkage in PLA fiber samples according to Aou and al.…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation